2022
DOI: 10.1038/s41598-022-14576-1
|View full text |Cite
|
Sign up to set email alerts
|

Decadal trends in 137Cs concentrations in the bark and wood of trees contaminated by the Fukushima nuclear accident

Abstract: Understanding the actual situation of radiocesium (137Cs) contamination of trees caused by the Fukushima nuclear accident is essential for predicting the future contamination of wood. Particularly important is determining whether the 137Cs dynamics within forests and trees have reached apparent steady state. We conducted a monitoring survey of four major tree species (Japanese cedar, Japanese cypress, konara oak, and Japanese red pine) at multiple sites. Using a dynamic linear model, we analyzed the temporal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…However, much longer monitoring and modeling analyses in forests with the same initial deposition levels of 137 Cs have revealed that, the activity concentration of 137 Cs is higher even in the inner tree parts, such as the sapwood, of konara oak than in Japanese cedar [e.g., Ohashi et al (2022) 18 ; they analyzed samples from plots KU1-S and KU1-Q]. Moreover, the increasing trends in this activity concentration in konara oak have been estimated to continue much longer 54 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, much longer monitoring and modeling analyses in forests with the same initial deposition levels of 137 Cs have revealed that, the activity concentration of 137 Cs is higher even in the inner tree parts, such as the sapwood, of konara oak than in Japanese cedar [e.g., Ohashi et al (2022) 18 ; they analyzed samples from plots KU1-S and KU1-Q]. Moreover, the increasing trends in this activity concentration in konara oak have been estimated to continue much longer 54 .…”
Section: Discussionmentioning
confidence: 99%
“…The uptake of 137 Cs from soil to trees is often evaluated by using an aggregated transfer factor, namely, the ratio of the 137 Cs activity concentration in each tree part to the 137 Cs inventory in the soil (unit: m 2 kg −1 ) 18 , 54 , 55 . In 2015, when the impact of the initial 137 Cs deposition would have been diminished, this ratio for oak trees was similar to, or greater than, that for cedar trees 55 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations